Digital Storytelling as Innovative Tool in Teaching Public Speaking Course at Mts Al Amiriyyah Banyuwangi - Agustin, Niken; Faruq, Ahmad (Universitas Negeri Semarang, 2025)
This research shows that in this digital era, education is required to switch from traditional methods to more innovative ways in improving students' abilities such as digital storytelling in learning public speaking at MTs Al Amiriyyah Banyuwangi is effective in improving speaking skills and understanding English texts. This study uses a qualitative approach with a case study design, involving 2 public speaking skills teachers and 45 students from two classes at MTs Al Amiriyyah Banyuwangi. Data were collected through in-depth interviews, classroom observations. Data analysis was carried out thematically to identify themes such as student confidence and creativity. The validity of the data is maintained through triangulation, which involves the use of several data collection techniques, including in-depth interviews, observations, and documentation. By combining these methods, this study is able to cross-check and validate findings, ensuring a more comprehensive and reliable understanding of the implementation of digital storytelling in public speaking training at MTs Al Amiriyyah Banyuwangi. The results of the study show that the application of digital storytelling has a significant effect in improving students' public speaking skills. This helps students understand the structure of the story, so that the speech becomes more organized and engaging. In addition, digital storytelling boosts students' confidence through visual and narrative elements, which makes them more comfortable speaking in front of an audience. This method contributes to the mastery of technological skills, such as video editing and presentation creation, that are relevant to the needs of the digital age.